Health and quality of life promotion for old people using bodily practices - Colom Toldrá, Rosé; Guimarães Cordone, Renata; de Almeida Arruda, Bruna; Fagundes Souto, Ana Cristina (O Mundo da Saúde, 2014)
The increasing of the elderly population is related to better material conditions for survival and progress of health practices. Bodily practices are recognized as an important strategy for health promotion and disease prevention for this population. This study aims to analyze the benefits of participating in groups of bodily practices under the perspective of Meir Schneider’s Self-healing technique, developed with adults and the elderly. Groups took part from March to September 2012 in twelve meetings, coordinated by the INTEGRA Laboratory of the Occupational Therapy School at the University of São Paulo. A semi-structured questionnaire and the SF-36 were used. There were 25 participants; most of them women (88%), with an average age of 65.8 years (ranging from 57 to 76) and an average of 3.6 years of education. Most participants performed the guidelines taught in the group at home, with referred physical, mental and emotional benefits. There were statistically significant improvements in SF36’s physical, emotional and bodily pain domains. The effects on the mind-body relationship were identified by positive results in all domains of the SF-36 and the semi-structured questionnaire. Results indicate that the method used is effective and beneficial for functional capacity and quality of life of this population.